Recurrent homozygous deletion of DROSHA and microduplication of PDE4DIP in pineoblastoma - Snuderl, Matija; Kannan, Kasthuri; Pfaff, Elke; Wang, Shiyang; Stafford, James M.; Serrano, Jonathan; Heguy, Adriana; Ray, Karina; Faustin, Arline; Aminova, Olga; Dolgalev, Igor; Stapleton, Stacie L.; et al. (Nature Communications, 2018)
Pineoblastoma is a rare and highly aggressive brain cancer of childhood, histologically belonging to the spectrum of primitive neuroectodermal tumors. Patients with germline mutations in DICER1, a ribonuclease involved in microRNA processing, have increased risk of pineoblastoma, but genetic drivers of sporadic pineoblastoma remain unknown. Here, we analyzed pediatric and adult pineoblastoma samples (n = 23) using a combination of genome-wide DNA methylation profiling and whole-exome sequencing or whole-genome sequencing. Pediatric and adult pineoblastomas showed distinct methylation profiles, the latter clustering with lower-grade pineal tumors and normal pineal gland. Recurrent variants were found in genes involved in PKA- and NF-κB signaling, as well as in chromatin remodeling genes. We identified recurrent homozygous deletions of DROSHA, acting upstream of DICER1 in microRNA processing, and a novel microduplication involving chromosomal region 1q21 containing PDE4DIP (myomegalin), comprising the ancient DUF1220 protein domain. Expresion of PDE4DIP and DUF1220 proteins was present exclusively in pineoblastoma with PDE4DIP gain., Pineoblastoma is a highly aggressive and rare childhood brain cancer, and the genetic drivers of sporadic pineoblastoma are unknown. Here, the authors genomically interrogated pediatric and adult pineoblastomas and found novel variants including recurrent homozygous deletions of DROSHA.